Evaluation of efficiency of innovation activity of an industrial Enterprise - Ponomaryov, V. D. (Teadmus OÜ, Estonia, 2024)
The report proves that the efficiency of innovation activity of an industrial enterprise is determined not only by financial indicators, but also by technical, economic, social and environmental aspects. Taking into account all these factors allows you to see a complete picture of the impact of innovations on the enterprise and make more informed decisions on the development of innovative projects.
Keywords: innovation; efficiency; evaluation; finance; productivity; industrial enterprises